Predictors of referral to the North Carolina Infant‐Toddler Program among infants with birth defects and infants born extremely preterm or low birthweight. Issue 18 (4th September 2019) - Forestieri, Nina E.; Van Buren, Eric; Simpson, Barbara D.; Meyer, Robert E.
Abstract: Background: North Carolina's Infant‐Toddler Program (NC ITP) provides Early Intervention (EI) services from birth to age three for children at risk for developmental delays. This study examined referral patterns by clinical and sociodemographic characteristics among infants with birth defects and infants born extremely preterm (gestational age < 27 weeks) or extremely low birthweight (<1, 000 g). Methods: A retrospective cohort of North Carolina resident births from 2012 to 2014 was matched to data from the North Carolina Birth Defects Monitoring Program and NC ITP records. A total of 2, 463 infants with eligible birth defects and 2, 118 extremely preterm or low birthweight infants were identified. Adjusted odds ratios and 95% confidence intervals from multivariable logistic regression models were used to analyze differences in referral by sociodemographic and clinical factors. Referrals resulting in enrollment were also examined. Results: About 70% of infants with eligible birth defects and 85% of extremely premature infants were referred to the NC ITP. Geographic region, maternal race/ethnicity, maternal and infant enrollment in Medicaid, and hospital level of care at delivery were associated with referral among both at‐risk groups. Among infants with birth defects, maternal age, education, and marital status were also associated with referral, as well as gestational age, birthweight, and the presence of multiple anomalies. Of the infants with referrals, over 80% in each group were subsequently enrolled. Conclusions: Many of the sociodemographic and clinical factors examined were associated with EI referral. These findings can be used to address coverage gaps and improve referral and enrollment rates for at‐risk infants.